PERANCANGAN SISTEM INFORMASI MANAJEMEN INVENTORI BERBASIS WEB (STUDI KASUS: SMK YPT PURWOREJO) - Dhika Widiyanto (Politeknik Sawunggalih Aji, 2022)
Web-based school asset management such as a web-based Inventory Management Information System is needed so that it can be a solution for managing data and information on assets and goods that have been recorded manually. The web-based Inventory Management Information System really helps the process of recording goods, starting from the procurement of goods, borrowing, returning, repairing goods to the procurement of consumables which have been recorded manually. The web-based Inventory Management Information System is expected to facilitate reporting of asset and goods management in schools, especially SMK YPT Purworejo